Professor Anwar Masood: A prominent figure of Humerous poetry - Dr. Memuna Subhani; Zahid Majeed Amjad (Zaban-o-Adab, 2021)
In the field of Urdu poetry the name of Prof. Anwar Masood is a guide line for the new comers. Prof. Anwar Masood’s poetry especially such poetry comprises humor, satire and irony is the symbol of his excellence and of the greatest quality. The draw backs of civilization and society are the major topics of his poetry. Qatah Nigari (Stanza writing) is the specialty in his poetry. The use of stanza writing in satire and journalism has added its significance Prof. Anwar Masood’s style is matchless. He has written some classic parodies. Its significance showed the social issues in Anwar Masood’s Poetry.